THE PHENOMENON OF WAR AND ROLE IN HUMAN DEVELOPMENT IN THE BOOKS OF NOBEL LAUREATES - Ibrokhimova Nodira Shukhratjonovna (Modern American Journals, 2025)
This article explores the phenomenon of war and its role in human spiritual development as reflected in the works of Nobel Prize laureates. It analyzes war not merely as a symbol of destruction or violence, but as a profound moral and philosophical experience that tests human conscience, values, and inner strength. Through examples from Ernest Hemingway’s A Farewell to Arms and Svetlana Alexievich’s The Unwomanly Face of War, the study examines how war exposes the moral dilemmas, emotional trauma, and psychological transformation of individuals. The article emphasizes that these literary works transform war from a historical event into a metaphysical category—a means of understanding the human condition, ethical responsibility, and the process of spiritual formation. Ultimately, war in Nobel literature is seen as a catalyst for self-realization and moral renewal, where the human spirit confronts and transcends suffering to attain inner harmony.
Keywords: Nobel Prize laureates, war and literature, human spiritual development, moral consciousness, philosophical interpretation of war, Ernest Hemingway, Svetlana Alexievich, human dignity, ethical transformation, moral experience.